The Effect of Alumunium Dust Exposure on Lung Function Disorders - Rinto Mangitua Hutapea; Novrikasari Novrikasari; Mona Lestari; Anita Camelia; Desheila Andarini; Rizka Faliria Nandini (Jurnal Respirologi Indonesia, 2021)
Background: Industrial development continues to increase every year. CV X is a company in the manufacture of cauldrons and prickles which produce aluminum dust contaminants. Workers who work more than eight hours and lack of air exchange can affect lung function. This study aims to analyze the effect of aluminum dust exposure on lung function disorders in workers at CV X. Methods: This type of research was quantitative study with cross-sectional design. Sampling using simple random sampling technique according to inclusion and exclusion criteria with 40 respondents. Data analysis by using univariate and bivariate analysis with Chi-Square and Kolmogorov-Smirnov tests. Results: The results showed that there was no effect of aluminum dust exposure on lung function disorders (p = 0.166). However, there are 65% of workers who have lung function disorders, consists of 42.5% obstructive workers, 22.5% restrictive workers, and none of which have impaired combined lung function, while 35% of workers is normal. The majority of aluminum dust levels in the work environment are above the Threshold Value (5 mg/m3) of 72.5%. Conclusion: It is known that workers who experience obstruction problems of 51.7% are workers that exposed to aluminum dust above TLV (5 mg/m3) and there are 24.1% of workers experiencing restriction disorders exposed to aluminum dust above TLV. To prevent workers from experiencing lung function disorders due to exposure to aluminum dust, it is necessary to control efforts in the form of additional ventilation to reduce dust levels in the work environment.